ANALISA KEANDALAN SISTEM BAHAN BAKAR MOTOR INDUK PADA KM. LEUSER - Hadi, Eko Sasmito; Budiarto, Untung (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2008)
Fuel oil system is one of the vital main engine supporting systems of MV. Leuser because this system is directly influence the main engine performance. The failure of fuel system should be the main engine shut down. The bigger affect was the ship could not be operated so the financial lost would be occurred. The aim of the research is an analysis the fuel system by approximation on reliability based. An analysis of the system was using qualitative and quantitative approximation. Qualitative analysis could be achieved by the Failure Mode and Effect Analysis (FMEA) and the Fault Tree Analysis (FTA). The quantitative analysis could be achieved by the Monte Carlo simulation. The resulted of the research, severity components such as filter, separator, transfer pump and booster pump was obtained by the severity classification and failure probability. The simulation would be achieved the value availability at 0.97 and the value of MTTFF (Mean Time to First Failure) is 2423.8363 hours. The simulation used some scenarios, the system availability would be more decrease if there were more stand by components occur the failure in the one of the components at 0,893.